2009
DOI: 10.1017/s0266467409006142
|View full text |Cite
|
Sign up to set email alerts
|

Soil-particle selection by the mound-building termiteMacrotermes bellicosuson a sandy loam soil catena in a Nigerian tropical savanna

Abstract: Many species of termite (Isoptera) build their nests inside mounds because a mound has direct and positive feedback effects on the termite colonies through the maintenance of humidity and protection of the population from enemies, e.g. ants (Jouquet et al. 2006, Korb 2003, Noirot & Darlington 2000). Soil manipulation by termites (Isoptera) for mound construction is of particular interest for many researchers in terms of pedogenesis of the tropics (Lavelle et al. 1992, Lobry de Bruyn & Conacher 1990). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 17 publications
4
30
1
Order By: Relevance
“…1) support Mahaney et al (1999) and Ketch et al (2001), who found only subtle differences in clay mineralogy between the mound structures and adjacent soils. These data represent a contrasting evidence to that of soil particle distribution data in Table 1 that showed substantial enrichment with clay particles in the mound structures relative to the adjacent natural soil horizons (Abe et al 2009a(Abe et al , 2009b. Moreover, we found very little difference in clay mineralogy between the mound wall and the hive (Fig.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…1) support Mahaney et al (1999) and Ketch et al (2001), who found only subtle differences in clay mineralogy between the mound structures and adjacent soils. These data represent a contrasting evidence to that of soil particle distribution data in Table 1 that showed substantial enrichment with clay particles in the mound structures relative to the adjacent natural soil horizons (Abe et al 2009a(Abe et al , 2009b. Moreover, we found very little difference in clay mineralogy between the mound wall and the hive (Fig.…”
Section: Discussioncontrasting
confidence: 86%
“…These samples include the external wall and main body of the hive in epigeal mounds of the fungusgrowing termite Macrotermesbellicosus (Smethman), Macrotermitinae (Termitidae), a very common termite species in the study area (Wood et al 1977, Collins 1979, 1981 and the near-surface (Ap2) and subsoil (Bwg3, Btg2 or Bt) horizons in a termite-free pedon at least 2 m away from the mound at three different toposequence positions: the valley bottom (08˚98 89 N, 06˚00 02 E); the hydromorphic fringe (08˚98 96 N, 06˚00 15 E); the well-drained upland plateau (08˚99 52 N, 06˚00 37 E) in a benchmark inland valley (see Table 1). As highlighted in the previous papers (Abe et al 2009a, 2009b, Abe and Wakatsuki, 2010, our sampling scheme has the following advantages: most previous reports simply compared the clay mineralogy of termite mounds (mostly the mound wall) with adjacent topsoils only, in spite of the fact that termites preferentially use subsoil material for mound construction (Lobry de Bruyn and Conacher 1990) and that the soil properties of termite mounds vary substantially according to structural units within the mound (Abe et al 2009a, 2009b, Abe and Wakatsuki, 2010.…”
Section: Study Site and Soil Samplesmentioning
confidence: 77%
See 2 more Smart Citations
“…This soil is comprised of predominantly kaolinite and quartz in the clay and fine-sand fractions, respectively (Abe et al 2006(Abe et al , 2007, and is classified in the order Ultisols or sandy, kaolinitic, isohyperthermic Typic Kandiustults in detail (Soil Survey Staff 2006). M. bellicosus, the target species of this study, is one of the dominant termite species in the study region and often builds large epigeal mounds that display various types of cathedral shape (Collins 1979(Collins , 1981Korb 2003;Abe et al 2009aAbe et al , 2009b.…”
Section: Site Descriptionmentioning
confidence: 99%